Lesion sterilization and tissue repair (LSTR) method in irreversible dental pulp changes of primary teeth - Zukanović Amila; Bajrić Elmedin; Marković Nina; Duratbegović Damir; Katana Elma; Čengić Emina; Serhatlić Senka; Pejak Hasan (Balkan Stomatological Society, 2023)
Background/Aim: Deep carious lesions on primary teeth usually have been causing infectious dental pulp changes. If indicated, traditional endodontic root canal treatment for these kinds of pulpal infections in primary teeth usually should involve the performing of pulpectomy methods, but often with questionable prognosis. The lesion sterilization and tissue repair (LSTR) approach is one of the good endodontic therapeutic alternatives for affected primary teeth with a poor prognosis, which could otherwise be condemned to premature extraction. Aim was to evaluate the medium-term clinical success in everyday practice of the LSTR method applied in affected primary teeth with irreversible pulpal tissue infections by observation of reduction/absence of their clinical symptoms. Material and methods: The study sample included child patients who had one or more of their affected primary molars with irreversible pulpal tissue changes of poor prognosis treated with the LSTR method. For each patient whose primary molar tooth was endodontically treated with the LSTR method a clinical evaluation of treated tooth was performed at intervals of 1 and 12 months afterwards. Results: Study sample was consisted of 40 child patients aged 4 to 9 years, with 45 primary molars included in total. It was obvious that the symptoms related to affected sample teeth have already been decreased almost immediately after initial action of triple antibiotic paste. Final outcome after 12-months follow-up period was success of applied LSTR method in 43 (95.6%) affected sample teeth in a way that initial clinical symptoms completely decreased and disappeared. Conclusions: LSTR method has been shown as successful pulpotomy technique for noninstrumental endodontic approach in non-vital pulp treatment of primary molar teeth in a 12-months follow-up period.